Mobility management for seamless handover in carrier aggregation heterogeneous networks deployment scenario of long term evolution-advanced - Ahmed-Abdulazeez, Mariam Ovayioza (2018)
Accessibility of spectrum is a fundamental challenge in future generation networks as current cellular networks suffer severe bandwidth congestion. The Long Term Evolution (LTE)-Advanced which is a roadmap to future generation networks are designed to achieve high data rates, ultra-low latency and improves spectrum usage efficiency. These cannot easily be achieved as no single network operator can provide the required contiguous spectrum for wider bandwidth. Also, insufficient macro base station (eNodeB) coverage, presents another challenges that result in high outage probability and low spectral efficiency. In line with these problems, Third Generation partnership project (3GPP) enabling technologies such as Carrier Aggregation (CA) is envision to tackle the problem of Spectrum inadequacy and high outage probability. CA is a technique where multiple component carriers (CCs) are aggregated and jointly used to improve transmission reliability and spectral efficiency. Therefore, the desire to achieve high data rates by increasing the transmission bandwidths over those that can be supported by a single carrier or channel becomes a necessity. 3GPP have standardized some classical Carrier Aggregation Deployment Scenarios (CADS) in release 10 to 12 (Rel. 10 to 12) to provide wider coverage, enhance system throughput and reduces outage probability using fixed Modulation and Coding Scheme (MCS). These CADS still provide low spectral efficiency and high outage probability because of the insufficient contiguous macro station (eNodeB) coverage and using of fixed MCS. So, achieving the expected capacity and system throughput enhancement is still a challenge. Therefore, this study proposes a new Carrier Aggregation Deployment Scenarios (CADSs) that utilizes Component Carriers (CC) from different spectrum bands to increase the overall transmission bandwidth and connection reliability. Meanwhile, CA technique induces a new handover scenario in which by employing Hard Handover (HHO) scheme may result to high Handover Probability (HOP), Ping- Pong Handover (PPHO) effect, radio Link failure, outage probability and throughput degradation. Load Balancing Optimization (LBO) and Handover Parameter Optimization (HPO) functions have also been included in the LTE-Advanced standard to minimize handover related issues. But issues related to non-optimal algorithm for selecting the appropriate Handover Control Parameters (HCPs) needs further attention. Attaining an optimal solution for HCPs selection is subjected to compromise between LBO and HPO functions, thus leading to inefficient handover decision making. Therefore, the objective of the research is to propose an enhanced CADS (Het-Nets) and implement efficient adaptive handover techniques in LTE-Advanced system. Firstly, a novel Het-Nets CADS is proposed, integrated with Adaptive Modulation and Coding with Cell Range Expansion (AMC-CRE) scheme. Secondly, a Hybrid Handover Parameters Optimization algorithm based on Enhanced Weight Performance (HHPO) is introduced to optimize, select suitable Handover Control Parameters (HCP) and to manage the conflict that may occur among self-optimization functions. Finally, multiple criteria Handover Decision (MC-HOD) algorithm is proposed to take an intact decision on handover execution. System level simulation results show that the Het-Net CADS with the integration of AMC-CRE scheme outperformed the other CADS considered in this work in terms of spectral efficiency and outage probabilities. The HHPO and the MC-HOD algorithms achieves significant enhancement compared to the conventional and other algorithms examined. Moreover, Het-Net CADS enhanced spectral efficiency up to 98%, 31% and 51%, while the outage probability is reduced by 25.5%, 57% and 56% over 3GPP’s CADSs #1, CADS#5 and CC-CADS respectively.